2023
DOI: 10.3390/molecules28083630
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid A Improves Rat Kidney Injury by Regulating MAPKs and TGF-β1/Smads Signaling Pathways

Abstract: Salvianolic acid A (SAA) is one of the major components in Salvia miltiorrhiza Bge., with various pharmacological activities, and is likely to be a promising agent for the treatment of kidney diseases. The purpose of this study was to explore the protective effect and mechanisms of SAA on kidney disease. In this study, the improvement effects of SAA (10, 20, 40 mg/kg, i.g.) on kidney injury rats were investigated by detecting the levels of KIM-1, NGAL in serum and UP in the urine of AKI model rats established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…MDA content can directly reflect the degree of body injury [ 41 ]. Oxidative stress is positively correlated with MDA levels [ 42 ]. The effect of the AMPK/mTOR signaling pathway on the protection of cordyceps sinensis against acute lung injury induced by acute kidney injury showed that MDA and BUN levels increased after renal injury ( p < 0.01) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA content can directly reflect the degree of body injury [ 41 ]. Oxidative stress is positively correlated with MDA levels [ 42 ]. The effect of the AMPK/mTOR signaling pathway on the protection of cordyceps sinensis against acute lung injury induced by acute kidney injury showed that MDA and BUN levels increased after renal injury ( p < 0.01) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…MDA content can directly reflect the degree of body injury [41]. Oxidative stress is positively correlated with MDA levels [42]. The effect of the AMPK/mTOR signaling pathway on the protection of cordyceps sinensis against acute lung injury induced by acute Clinically, the concomitant nephrotoxicity and hepatotoxicity caused by CTX limit its therapeutic effects, and CTX induces inflammation by increasing the activities of tumor necrosis factor-α (TNF-α), nuclear factor-κB (NF-κB), interleukin-6 (IL-6), and inducible nitric oxide synthase (INOS) [45].…”
Section: Effects Of Biochemical Indices Of Kidney Injurymentioning
confidence: 99%
“…The experimental protocol used in this study was approved by the Animal Ethics Committee of Shenyang Pharmaceutical University. The routine experiments were performed in accordance with the “Regulations on the Management of Laboratory Animals” issued by the National Science and Technology Commission [ 16 ]. Neonatal Sprague-Dawley rats were used for OGD/R experiments to culture primary cortical neurons.…”
Section: Methodsmentioning
confidence: 99%
“…More and more studies have shown that salvianolic acid A ( 17 ) is likely to be a promising agent for the treatment of kidney diseases. For example, Diao et al reported that salvianolic acid A ( 17 ) played a significant role in improving kidney injury in rats, and the mechanism may be achieved by regulating the MAPK and TGF-β1/Smad protein (Smad) signaling pathways [ 122 ]. In addition, salvianolic acid A ( 17 ) could significantly reduce the levels of anti-Sm-IgG and IgM antibodies and attenuate prostaglandin-induced histopathological alterations in the kidneys of BALB/c mice by inhibiting the phosphorylation of inhibitory kappa B kinase (IKK), I-κB, and NF-κB, thereby improving renal function [ 123 ].…”
Section: Effects Of Salvianolic Acid Components On Immune Systemmentioning
confidence: 99%